Esther Waters - Moore, George (London : c)
This 1948 film is based on the best-known novel of the Irish writer George Moore, known for his unflinching realism. It tells the story of a servant girl in Victoria England who is seduced by a squire and then abandoned. Alone and pregnant, she returns to London. There she struggles to raise her child on her own. Starring Kathleen Ryan, Dirk Bogarde, and Cyril Cusack. Directed by Ian Dalrymple and Peter Proud.
Keywords: Unmarried mothers -- Fiction; Mothers and sons -- Fiction; Women household employees -- Fiction